Multi-layered UL700 arch-grid module with inelastic buckling for localized reinforcement of soft ground. (August 2017) - Lee, Dongkyu; Lee, Jaehong; Doan, Quoc Hoan
Highlights: Inelastic buckling and modal analysis are presented to design optimal shape and size of the steel arch-grid module for localized reinforcement of soft ground. The multi-layered detail and construction method of steel arch-grid module are newly evaluated for localized reinforcement of soft ground. The high strength UL700 and normal strength SS400 are compared to find appropriate arch-grid structures. Numerical examples investigate optimal shape and size of multi-layered arch-grid structures in both linear and nonlinear buckling behaviors using SAP2000 software. Abstract: This research proposes the inelastic buckling and modal analysis to design optimal shape and size through UL700 steel arch-grid unit module which is for localized reinforcement of soft ground. The optimal arch-grid design is achieved among its most efficient design possibilities such as different plate type, extended grid, multi-story grid, combined grid. The steel arch-grid unit module is composed of a vertical member and a board member combined with the top and bottom sides of the said vertical member, including the horizontal member equipped with multiple arm parts combined with the center part into one body in the shape of a cross. The construction method for reinforcement of soft ground is proposed in detail in this research. Numerical experiments are provided to survey optimal shape and size of arch-grid structures with differential models applied to buckling analysis, modal and static load, in consideration of both linear and nonlinear behaviors, by using SAP2000 version 15.0.1 software. With sufficient features of steel arch-grid for supporting structural foundations, this research suggests the possibility of requiring more studies and of providing more applications in the field of constructional structures.